A broader training for medical receptionists - Anderson, Patrick McC. D. (1980)
A course for 40 medical receptionists working in general practice was arranged at a local postgraduate centre. The curriculum was divided into two sections. The first dealt with the traditional, factual side of medical reception work and the second was concerned with the human behaviour aspect of a receptionist's work. It seems that there was some benefit to the receptionists from their experience of both aspects of this course.